2016
DOI: 10.1111/ijlh.12454
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of BECN1 in acute myeloid leukemia: association with distinct cytogenetic and molecular abnormalities

Abstract: Overall, remarkable association of reduced expression of BECN1 with FLT3-ITD mutation and monosomal karyotype and their functional relationship is interesting which should be addressed and verified in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
4
7
0
Order By: Relevance
“…In AML patients, reduced BECN1 gene expression was associated with older age and higher TLC. Our values were very close to the findings of Zare-Abdollahi et al [17], who reported a mean age of 52.9 years and a mean TLC of 52.6 × 10 3 /μl in AML patients with reduced BECN1 gene expression. However, we did not observe a significant relationship between the level of BECN1 gene expression and sex, haemoglobin level, or platelet count.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In AML patients, reduced BECN1 gene expression was associated with older age and higher TLC. Our values were very close to the findings of Zare-Abdollahi et al [17], who reported a mean age of 52.9 years and a mean TLC of 52.6 × 10 3 /μl in AML patients with reduced BECN1 gene expression. However, we did not observe a significant relationship between the level of BECN1 gene expression and sex, haemoglobin level, or platelet count.…”
Section: Discussionsupporting
confidence: 91%
“…Upon detailed analysis, we found that 72.0% of the patients had reduced BECN1 gene expression compared to the control group and that 28.0% of the patients had normal BECN1 gene expression. This result is in accordance with Zare-Abdollahi et al [17], who analysed the expression status of the BECN1 gene in a series of 128 de novo AML patients using real-time quantitative polymerase chain reaction, in which BECN1 reduced expression was detected in 57 of the 128 cases (45%). In another study performed by Mohamadimaram et al [18], expression of other autophagy genes (namely, ATG7 and light chain 3 (LC3)) was investigated, and the authors found a significant decrease in expression levels of both genes in most AML patients (81.81% and 75.55%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Two previous studies have described an association between low expression at the mRNA level of single autophagic regulators and an adverse prognosis. First, BECN1 is important for the initiation and advance of autophagy, and reduced BECN1 mRNA levels were associated with an adverse prognosis, FLT3-ITD, monosomal karyotype and high age [88]. Second, decreased BECN1 mRNA expression is also associated with an adverse prognosis [89].…”
Section: Discussionmentioning
confidence: 99%
“…Beclin 1 and LC3 are reportedly down-regulated in AML cells compared to normal cells [26]: with Zare-Abdollahi et al [8] verifying that Beclin 1 down-regulation is associated with the FLT3-ITD fusion in AML patients. In addition, low ULK1-expression patients had higher WBC counts than the high ULK1 group.…”
Section: Clinical Characteristics Of Aml Patientsmentioning
confidence: 83%